Borexino Results on Neutrinos from the Sun and Earth - Sindhujha Kumaran; Livia Ludhova; Ömer Penek; Giulio Settanta (Universe, 2021)
Borexino is a 280-ton liquid scintillator detector located at the Laboratori Nazionali del Gran Sasso in Italy. Since the start of its data-taking in May 2007, it has provided several measurements of low-energy neutrinos from various sources. At the base of its success lie unprecedented levels of radio-purity and extensive thermal stabilization, both resulting from a years-long effort of the collaboration. Solar neutrinos, emitted in the Hydrogen-to-Helium fusion in the solar core, are important for the understanding of our star, as well as neutrino properties. Borexino is the only experiment that has performed a complete spectroscopy of the pp chain solar neutrinos (with the exception of the hep neutrinos contributing to the total flux at <semantics>10−5</semantics> level), through the detection of pp, <semantics>7</semantics>Be, pep, and <semantics>8</semantics>B solar neutrinos and has experimentally confirmed the existence of the CNO fusion cycle in the Sun. Borexino has also detected geoneutrinos, antineutrinos from the decays of long-lived radioactive elements inside the Earth, that can be exploited as a new and unique tool to study our planet. This paper reviews the most recent Borexino results on solar and geoneutrinos, from highlighting the key elements of the analyses up to the discussion and interpretation of the results for neutrino, solar, and geophysics.